Patagonin-CRISP: Antimicrobial Activity and Source of Antimicrobial Molecules in Duvernoy’s Gland Secretion (Philodryas patagoniensis Snake) - Badari, Juliana Cuoco; Díaz-Roa, Andrea; Teixeira Rocha, Marisa Maria; Mendonça, Ronaldo Zucatelli; Silva Junior, Pedro Ismael da (Frontiers in Pharmacology, 2021)
Snake venoms contain a variety of toxins with a range of biological activity. Among these are the cysteine-rich secreted proteins (CRISPs). The proteins of this family have masses of 20–30 kDa and display homologous amino acid sequences containing 16 cysteine residues, forming eight disulfide bonds. Some of these proteins have been explored, characterized, and described in terms of their activity; however, little is known of their range of activities. A search for new antimicrobial molecules is ongoing, as the number of microbial strains resistant to available antibiotics is increasing. We identified antimicrobial activity in the secretion of the Duvernoy’s gland of the rear-fanged Philodryas patagoniensis. Fractions of this venom were subjected to Reverse Phase – High Performance Liquid Chromatography and analyzed to determine their antimicrobial activity with a liquid broth inhibition assay. One of the fractions presented activity against a Gram-negative bacterium and a filamentous fungus. This fraction was analyzed with LC-MS/MS, and a protein of 24,848.8 Da was identified. Database searches allowed us to identify it as a CRISP due to the presence of some unique fragments in the molecule. We called it patagonin-CRISP, as the same protein in the venom of P. patagoniensis had previously been characterized as having a different biological activity. Patagonin-CRISP presented activity at very low concentrations and showed no cytotoxic activity. This is the first time that antimicrobial activity has been identified for P. patagoniensis venom or for a CRISP family protein.